Guidance Note For Developing Government Local Currency Bond Markets. (International Monetary Fund, 2021)
This guidance note was prepared by International Monetary Fund (IMF) and World Bank Group staff under a project undertaken with the support of grants from the Financial Sector Reform and Strengthening Initiative, (FIRST).The aim of the project was to deliver a report that provides emerging market and developing economies with guidance and a roadmap in developing their local currency bond markets (LCBMs). This note will also inform technical assistance missions in advising authorities on the formulation of policies to deepen LCBMs.